1988
DOI: 10.1128/jcm.26.4.784-786.1988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nonisotopically labeled oligonucleotide probe to detect the heat-stable enterotoxin gene of Escherichia coli by the DNA colony hybridization test

Abstract: A commercially available, alkaline-phosphatase-conjugated oligonucleotide probe for detecting the heatstable enterotoxin gene of Escherichia coli was compared with cloned gene probes by examining E. coli isolates from traveler's diarrhea by DNA colony hybridization tests. The oligonucleotide probe was useful in specifically identifying the so-called STh gene. No deproteinization of sample was necessary to prepare the colony blots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…The NEP-010 nucleotide probe for STA (11) is 26 bases long and constitutes part of the STA2 gene sequence but differs in two bases from the analogous region of the STAI sequence. Previous reports have shown that this probe is satisfactory in colony hybridization tests for the detection of strains with the STA2 gene but does not identify all strains carrying the STAI gene (18,25). A mixed probe incorporating both STAl and STA2 enzyme-linked oligonucleotides was provided by Du Pont, NEN Research Products, Boston, Mass., at our request and was used to test the 200 strains.…”
mentioning
confidence: 99%
“…The NEP-010 nucleotide probe for STA (11) is 26 bases long and constitutes part of the STA2 gene sequence but differs in two bases from the analogous region of the STAI sequence. Previous reports have shown that this probe is satisfactory in colony hybridization tests for the detection of strains with the STA2 gene but does not identify all strains carrying the STAI gene (18,25). A mixed probe incorporating both STAl and STA2 enzyme-linked oligonucleotides was provided by Du Pont, NEN Research Products, Boston, Mass., at our request and was used to test the 200 strains.…”
mentioning
confidence: 99%
“…The purpose of this study was to characterize porcine ETEC strains belonging to different serogroups but all possessing the F4 fimbriae, with regard to enterotoxin and fimbrial adhesin encoding genes, by using enzyme-labelled and 32P-labelled oligonucleotide probes. The use of such probes has been shown to be an appropriate method for detecting ETEC, both from faecal specimens, on colony blots, and on Southern blots of plasmid profiles (HILL et al, 1986; JABLONSKI et a]., 1986; LI et a]., 1987; NISHIBUSHI et al, 1988;SOMMERFELT et al, 1988;WASTESON et al, 1988). As indicated from multilocus enzyme electrophoresis, the chromosomal gene diversity among E. coli isolates sharing single antigenic determinants, can approach or equal that observed by randomly chosen strains (CAUGANT et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Although hybridization tests using radioisotope-labeled DNA fragments may be useful for research laboratories, radioisotope management in routine clinical laboratories is difficult. To avoid this problem, various enzyme-labeled oligonucleotide probes are under investigation (8,18,29). In this study, we have developed a DNA hybridization method with an enzyme-linked oligonucleotide probe to detect mecA, mecA-ELONP.…”
mentioning
confidence: 99%